2020
DOI: 10.1002/jmr.2840
|View full text |Cite
|
Sign up to set email alerts
|

Entropy‐driven binding of octyl gallate in albumin: Failure in the application of temperature effect to distinguish dynamic and static fluorescence quenching

Abstract: Fluorescence quenching is widely used to obtain association constants between proteins and ligands. This methodology is based on assumption that ground-state complex between protein and ligand is responsible for quenching. Here, we call the attention about the risk of using the temperature criterion for decision of applying or not fluorescence quenching data to measure association constants. We demonstrated that hydrophobic effect can be the major force involved in the interaction and, as such, superposes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(82 reference statements)
2
1
0
Order By: Relevance
“…Hence, understanding the chiroptical behavior of these drugs when complexed with albumin can be essential data in the area. Besides being chiral, the binols are highly hydrophobic, an indicative solid that could be a ligand of HSA 20 . Our expectation was confirmed, and an alteration in the CD spectrum was observed experimentally and theoretically.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hence, understanding the chiroptical behavior of these drugs when complexed with albumin can be essential data in the area. Besides being chiral, the binols are highly hydrophobic, an indicative solid that could be a ligand of HSA 20 . Our expectation was confirmed, and an alteration in the CD spectrum was observed experimentally and theoretically.…”
Section: Introductionsupporting
confidence: 79%
“…Besides being chiral, the binols are highly hydrophobic, an indicative solid that could be a ligand of HSA. 20 Our expectation was confirmed, and an alteration in the CD spectrum was observed experimentally and theoretically.…”
Section: Introductionsupporting
confidence: 77%
“…33 In addition to that, previous studies have demonstrated that the gallol moiety of octyl gallate blocks the enzyme activity of α-amylase, squalene epoxidase, and lipoxygenase by non-specific binding to their active site. 34–39 Thus, the enzymatic resistance of Plu–GA micelles could help protect encapsulated hydrophobic drugs.…”
Section: Resultsmentioning
confidence: 99%